MODERN DIAGNOSTICS AND TREATMENT OF ACUTE STREPTOCOCCAL PHARYNGITIS AND TONSILLITIS IN CHILDREN AND ADULTS - T. V. Kulichenko; U. S. Patrusheva; A. A. Redina; M. A. Lazareva (Union of pediatricians of Russia, 2013)
The article discusses modern principles of diagnostics and treatment of acute streptococcal pharyngitis and tonsillitis in different age groups. It gives recommendations on using an express test for quick and quality diagnostics of infections caused by group A β-hemolytic streptococcus (GABHS) in routine practice. The introduction of recommendations on diagnostic and therapeutic tactics in adult patients into this article allows to resolve issues of managing family cases of GABHS-infection. Adequate conduct of GABHS express tests and rational selection of therapeutic measures at acute pharyngitis and tonsillitis reduces the risk of prescribing ungrounded antimicrobial therapy.